Evaluating the burden of head injuries on a rural emergency department in South Africa - Sannya Ramdheen; Bavani Naicker (South African Family Practice)
Background: Head injuries place a significant burden on the emergency department (ED) workload. This is prominent in low-middle income countries (LMICs), which have low resourced health systems and a skewed burden compared to global data. A large paucity of data exists among LMICs, therefore limiting comparisons on a global perspective. This study aimed to evaluate the ED burden of head injuries in a rural setting, within a LMIC.